TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION FOR SLOW LEARNERS IN INCLUSIVE PUBLIC SECONDARY SCHOOLS - Hariyati, Efa Nur; Seinsiani, Izzati Gemi (Jurnal Wawasan Pendidikan, 2026)
This study examines the strategies and challenges faced by teachers in teaching reading comprehension to slow learners in inclusive classrooms at a public secondary school in Semarang, Central Java. Utilizing a qualitative research design, data were collected through classroom observations using a checklist, as well as semi-structured interviews with two English teachers who teach inclusive classes in grades 7 and 8. Slow learners participated passively during the classroom observations. The data were analyzed thematically to identify patterns related to instructional strategies and challenges. The findings indicate that teachers implement various strategies to enhance reading comprehension for slow learners, including differentiated instruction through individualized lesson planning, the use of visual and audio media, vocabulary-focused instruction through drilling, scaffolding through step-by-step reading activities, and peer teaching. However, teachers also encountered several challenges, such as a lack of specific guidelines for inclusive education, limited time and class management issues, and students’ limited concentration and motivation. These findings contribute to the existing research on inclusive English language teaching and offer practical strategies for improving reading comprehension for slow learners in inclusive classrooms.